Analysis Of Teacher Strategies In Overcoming Primary School Students' Early Reading Learning Difficulties Using An Individual Approach - Irawati, Rika; Hadi, Sopiyan; Houtman, Houtman (Jurnal Ilmu Sosial Mamangan, 2024)
This research was conducted to describe the strategies used by class teachers in overcoming reading learning difficulties of second grade students at SD Negeri 1 Sri Tanjung. This research employs descriptive qualitative research methods in the form of a case study. Qualitative research is also referred to as a naturalistic research method, as it is conducted in natural conditions. The findings of the research and subsequent discussion lead to the conclusion that a form of learning difficulty, specifically reading difficulties, was identified in Class II SDN Sritanjung. The reading difficulties observed in the field are classified as low-level reading difficulties. The strategies employed by the class teachers are not optimal, as evidenced by the persistence of difficulties in learning to read and write among a significant proportion of students. The teacher's strategy for introducing beginning reading employs a multi-modal approach, integrating the thickening of letters, the word wall method, reading book media, and a range of activities, including letter and word games, singing, the question-and-answer method, and the assignment method.